A microstructuring route to enhanced thermoelectric efficiency of reduced graphene oxide films. (24th April 2019) - Mehmood, Tariq; Kim, Jin Ho; Lee, Do-Joong; Dizhur, Sergey; Odessey, Rachel; Hirst, Elizabeth S; Osgood, Richard M; Sayyad, Muhammad Hassan; Munawar, Munawar Ali; Xu, Jimmy
Abstract: Microstructuring of nanocomposites by methods such as corrugation and wrinkling is explored as a new tool to improve their thermoelectric efficiency of energy harvesting. Its effects include modulating a given composite's electrical conductivity and Seebeck coefficient. Here we demonstrate that corrugating and wrinkling a reduced graphene oxide thin film can give rise to an enhanced electrical conductivity as well as Seebeck coefficient which together results in an increased thermoelectric power factor. Specifically, wrinkling in two dimensions greatly increased both the Seebeck coefficient, up to 26%, and the power factor by almost an order of magnitude. The observed enhancements are attributable to an increased electrical network conductivity of the stacked reduced graphene-oxide flakes and a phonon drag effect associated with a higher packing density. This microstructuring route is simple yet effective in harvesting thermoelectric energies and can be naturally occurring in, highly scalable for, and applicable to flexible, stretchable and wearable electronics.